The Socio-environmental impacts of small-scale mining operations in the Tarkwa-Nsuaem municipality in Ghana - OPOKU MENSAH, Seth (KDI School, 2016)
Small-scale gold mining looked upon as a necessary evil has the potential of creating employment and generating revenue and hence economic growth and poverty alleviation. Smallscale gold mining operations are often unregulated and appear to be more destructive. It adversely impacts individuals, environment and communities with livelihood implications. The study therefore examined the socio-environmental impacts of small-scale gold mining operations in the Tarkwa-Nsuaem Municipality in Ghana. Data was obtained from households, miners, community leaders, Tarkwa-Nsuaem Municipal Assembly, the Minerals Commission and the Environmental Protection Agency by using questionnaires and interview guides. Secondary data sources were also used. The study revealed that miners use both underground and surface mining in extracting mineral ore. Though there are many small-scale gold mining companies/groups, only 15 are licensed with a greater majority operating at the blind side of the law in the Municipality. The study again brought to bare that the impacts of small-scale gold are both positive and negative. Positively, it generates employment, income, promotes local economic development, boosts trade and its profitable over other economic activities. However, its inefficient exploitation has brought about serious environmental damages that have affected the livelihoods of many households as well as threatening the socio-economic lives of the people. Individuals whom small-scale gold mining operations have affected adopt various coping strategies for their survival though not sustainable. Accordingly, it is important to regulate the activities of small-scale gold mining to make it sustainable and be able to harness its development prospects by putting in more efforts by all stakeholders especially the government.
Thesis(Master) --KDI School:Master of Development Policy,2016